BIMBINGAN BELAJAR GRATIS BAGI SISWA SEKOLAH DASAR NEGERI 177923 PARIKMATIA TAPANULI UTARA PASCA PEMBELAJARAN DARING - Jojor Silalahi; Uli Evianna Hutabarat; Andris Ompusunggu; Febri Dungo Silitonga; Yessi L M Hutabarat; Paramita Panjaitan; Seylah M. Sihombing (Bajang Institute, 2022)
One of the impact of pandemic Covid 19 in education is the learning lose. The learning lose mean that the student loss the education and skill in academic progress during almost two years the closure of face to face instruction. One solution that can minimalize the learning lose during the closure of face to face instruction is to give the students in school the tuition classes. In this article, we make the tuition classes after the school time as a community dedication from FKIP Universitas HKBP Nommensen Medan to SD Negeri 177923 Parikmatia, Tapanuli Utara, SUMUT from February 2 nd to 26 th, 2022. The tuition classes used student Oriented learning method by six students and one lecturer. The program has held successful where the students behave great benefits by the enhancing their competence in literacy and numeracy.